Glycemia monitoring - Basov, Igor; Švitra, Donatas (Nonlinear Analysis: Modelling and Control, 1998)
Here a system of two non-linear difference-differential equations, which is mathematical model of self-regulation of the sugar level in blood, is investigated. The analysis carried out by qualitative and numerical methods allows us to conclude that the mathematical model explains the functioning of the physiological system "insulin-blood sugar" in both normal and pathological cases, i.e. diabetes mellitus and hyperinsulinism.
Keywords: none